Random walks in the different sectoral submarkets of the Philippine Stock Exchange amid modernization - Rufino, Cesar C. (2013)
This study explores the weak-form efficiency of the Philippine Stock Exchange (PSE) and its different sectoral markets using modern inference techniques with robust statistical properties. The research is motivated by the lack of consensus in the literature on the informational efficiency of the country’s stock market and the apparent scarcity of studies on the same issue using data covering the period of massive modernization of the exchange, geared toward transparent disclosures and integrity of transactions. The study may also be considered a fitting assessment of why the PSE is setting the pace over most stock exchanges in Asia in terms of growth levels across key stock market indicators, culminating in a highly successful year 2012 when it ranked ninth among the ten best-performing stock markets of the world. Evidence presented by the results of the study suggests the presence of overall informational efficiency in the Philippine Stock Exchange during the period under review.
Keywords: Philippine Stock Exchange; Stocks -- Prices -- Econometric models